Pemikiran Tokoh Semiotika Modern - Rivaldi Abdillah (TEXTURA, 2021)
Semiotics is the study of everything about signs, signs are objects that always exist in people's daily lives. There were so many previous figures who discussed this sign, so that there were many perceptions of this sign science or so-called semioti. However, in semiotics, there are figures who are the founders of modern semiotics, namely Ferdinand De Sasussure and Charles Sanders Pierce. They are one of the figures who study semiotics. Ferdinand De Saussure is considered a central figure in semiotics, he was the first to use the term "semiology" (Europe) "semantics" (America), namely the science of signs and their use in society. Understanding. Ferdinand's theory of semiotics has been widely followed and developed. Many of the characters after Ferdinand De Saussure followed his theory and developed it broadly, so that the understanding of Semiotics was broader in scope. The figures of Modern Semiotics discussed here are the semiotic thoughts of Ferdinand De Saussure, Charles Sanders Pierce, Roman Jacobson, Louis Hjelmselv, Greimas, Roland Barthes, Halliday, and Umberto Eco.